Lean Assessment in Selected Furniture Manufacturing Companies - Ye Siang, Chiang; Atan, Siti Anisah (Research in Management of Technology and Business, 2020)
Malaysian furniture industry is facing striking issues relating to raw materials supply, workforce and sustainability. Strategic practices such as lean manufacturing will help the industry to stay competitive in global markets. However, lean practices are fairly new in Malaysian furniture manufacturing industry. So, this study is intended to assess lean status of selected companies in furniture manufacturing industry. Six companies located in Johor state were chosen as case study samples. Lean assessment tool developed by Strategos Incorporation was used to assess lean practices from nine key areas of manufacturing, namely: inventory, teams, process, maintenance, layout, supplier, setup, quality, and production control and scheduling. Data from the assessment questionnaire then keyed-in to an Excel template to calculate the results. The result of the assessment then visualized into a “radar chart”. The radar chart will impart the actual lean status verses the presumed lean accomplishment of the company. In general, lean is taking place in furniture manufacturing industry. From the nine keys area of manufacturing, on average, furniture manufacturing industry performs well in team approach, maintenance, setup and layout and handling. Other five key areas particularly quality and suppliers did not accomplish targeted lean status. Suggestion from this study is lean practices in furniture industry need some modifications from automotive originated lean due to distinctive character of the industry.